Lalani of the distant sea - Kelly, Erin Entrada (Greenwillow Books, 2020)
Twelve-year-old Lalani Sarita's mother falls ill from an incurable disease in their small island village of Sanlagita. Lalani is then faced with an impossible task--to journey across the sea to the prosperous, legendary Mount Isa and help save her mother and her island from natural calamities and disease. But although the deadly journey has claimed men and boys alike, including her own father, Lalani courageously sets sail in a small boat to save the ones she loves.